Telaah Singkat Tafsir Bi Al-Ma’tsur - Nurul Huda (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
The Qur'an is like a pearl, says Abdullah Darraz. The color of its light can reflect differently, depending on the angle from which it is viewed. It can be blue, purple, red, green, yellow, white, and so on, depending on the angle of the viewer or interpreter. And the angle of the interpreter is highly dependent on his personal scientific background, experience and inclinations. Therefore, interpretation is often considered to have elements of subjectivity of the interpreter. While in terms of its source, tafsir can be divided into tafsir bi al-ma'tsur and tafsir bi al-ra'y. The first uses a historical approach and the second uses a narrative approach. The first uses a historical approach and the second uses a reasoning approach. The first approach is considered the best and the second approach is considered risky, which even the Prophet threatened the culprit of hell if the interpretation process is done haphazardly without heeding the proper rules. Tafsir bi al-ma'tsur itself is sometimes in the form of interpretation of the Qur'an by the Qur'an itself, interpretation of the Qur'an by the Prophet and interpretation of the Qur'an by the Sahabat or Tabiin. For this reason, it is important to understand which and what are the characteristics of tafsir bi al-ma'tsur, which is the best interpretation.